KARAKTERISTIK TANAH LIAT DAN PENGARUHNYA TERHADAP KEBERHASILAN WARNA GLASIR - Yustana, Prima (CORAK, 2012)
This eksperiment attempts to solve common problems faced in ceramic finish, finishing ceramic objects have differences to resolve other matters. Glaze is a type of glass coating that is applied to coat the ceramic objects, this is an interesting layer to be studied, because the success glaze applications in ceramics is influenced by many factors.Applications glaze on ceramic objects have a very high level of difficulty, the difficulty seen in glaze formulas, application techniques, firing temperature, shrinkage of dry matter and the successful achievement of color after glaze the combustion process. This research is to determine whether the clay character has an influence on the success rate of the color will appear. The problem solving method uses the experimental method, this method is considered more appropriate to determine the level of success of an experiment relating to material containing chemical elements. Clay used is a type of stoneware clay has five classes of characters, clay are as follows: 1. Pacitan soil, wet soil has a reddish color, 2. Singkawang soil, wet soil has a whitish colour, 3. Sukabumi is a brightly colored ground, wet floor is a beige, with 4. Sukabumi, the dark ground, wet soil has a dark brown color, 5. Bojonegoro soil, wet soil has a light brown color. color Glaze five characters shall be applied on the surface of clay are: 1. young Greens, 2. Pink, 3. Greenish blue, 4. Brown 5. Dark blue. Character clay is relatively large contribution to the emergence of color glaze in accordance with the wishes or the plan, especially when using a formula based on the glossy glaze. Glaze formula will tend to be stable when there is a combination of stain with a glaze oxide, stable formula can also be found on the matt glaze, because it glaze was close or not transparent. coloring oxides are very sensitive to the character of soil temperature change is cobalt and fe ,experiment that required in advance if the formula contains two types of oxide glaze. Burning with the reduction or oxidation also will give effect to the glaze colors will appear. Keyword: experiment, color glaze, characters clay.